Aplicación de buenas prácticas de manufactura para el mejoramiento de la calidad del chifle en la microempresa “Rico Chifle” - Intriago Cabrera, Jhon Jairo (2021)
The objective of this research consisted of applying the Good Manufacturing Practices to check the safety of chifle, through a functional diagnosis in the microenterprise "Rico Chifle" where important aspects were evaluated for compliance with the standards and the subsequent accreditation of ARCSA. Before implementing the GMP, a compliance of 64.13 % and 35.87 % of non-compliance was observed in the evaluated parameters of the check list. The quality of the chifle was considered as a study variable. This research was descriptive, using techniques such as: check list, interview, statistical techniques, physicochemical and microbiological analysis. Once the personnel were trained on good manufacturing practices, 92.39 % compliance with GMP and 7.61 % non-compliance were verified. In the physical-chemical results; the results of pre-application of GMP, the fat in sample 3 (Chifle #3) obtained 5.14 %, which is outside the limit in the NTE INEN 2561 standard, while the results of the peroxide, moisture and microbiological index (molds and E. coli) are within the parameters indicated by the same standard. The post-application analyses are within the limits allowed by the aforementioned standard. The Pareto diagram shows 4 main problems: cleanliness of the operator when entering and leaving the production area, cleanliness of the equipment before and after each process, knowledge of the processes by the operators, temperature control; the binary logistic regression applied shows that there is an improvement in the quality of the chifle, concluding that the quality of the chifle improved with the corrections made in the microenterprise.